MEDIA INFORMASI DAN FORUM KOMUNITAS AIRSOFTGUN FAST JAMBI - Ezrifal Sany; Ihwan Kurnia Baiturahman (JURNAL AKADEMIKA)
As one part of the field of Community Airsoftgun FAST (Freelancer Airsoft Spring Team) Jambi airsoftgun sports information is required. It requires the media information in the Community Airsoftgun FAST (Freelancer Airsoft Spring Team) Jambi felt still less effective and efficient. Given the many obstacles in sports mensosialisikan airsoftgun, we analyze the form of study in one of the Community Airsoftgun FAST (Freelancer Airsoft Spring Team). The results of the study are needed Airsoftgun Community information media FAST (Freelancer Airsoft Spring Team), the input data is that the data members, photos, videos, units, scheduled to play, and the output is the result of photo documentation, video, data members, playing schedule, the unit used , By leveraging Web Programming as a programming language and SQL for data storage, built a new system in the form of Media Information and Community Forum Airsoftgun FAST Jambi, conclusions can be drawn after the writing of this report is produced a system that can assist in promoting airsoftgun community.